Human nasal septal chondrocytes (NSCs) preconditioned on NSC-derived matrix improve their chondrogenic potential - Yong Kwan Noh; Sung Won Kim; Ik-Hwan Kim; Kwideok Park (Biomaterials Research, 2021)
Abstract Background Extracellular matrix (ECM) has a profound effect on cell behaviors. In this study, we prepare a decellularized human nasal septal chondrocyte (NSC)-derived ECM (CHDM), as a natural (N-CHDM) or soluble form (S-CHDM), and investigate their impact on NSCs differentiation. Methods N-CHDM, S-CHDM were obtained from NSC. To evaluate function of NSC cultured on each substrate, gene expression using chondrogenic marker, and chondrogenic protein expression were tested. Preconditioned NSCs-loaded scaffolds were transplanted in nude mice for 3 weeks and analyzed. Results When cultivated on each substrate, NSCs exhibited similar cell spread area but showed distinct morphology on N-CHDM with significantly lower cell circularity. They were highly proliferative on N-CHDM than S-CHDM and tissue culture plastic (TCP), and showed more improved cell differentiation, as assessed via chondrogenic marker (Col2, Sox9, and Aggrecan) expression and immunofluorescence of COL II. We also investigated the effect of NSCs preconditioning on three different 2D substrates while NSCs were isolated from those substrates, subsequently transferred to 3D mesh scaffold, then cultivated them in vitro or transplanted in vivo. The number of cells in the scaffolds was similar to each other at 5 days but cell differentiation was notably better with NSCs preconditioned on N-CHDM, as assessed via real-time q-PCR, Western blot, and immunofluorescence. Moreover, when those NSCs-loaded polymer scaffolds were transplanted subcutaneously in nude mice for 3 weeks and analyzed, the NSCs preconditioned on the N-CHDM showed significantly advanced cell retention in the scaffold, more cells with a chondrocyte lacunae structure, and larger production of cartilage ECM (COL II, glycosaminoglycan). Conclusions Taken together, a natural form of decellularized ECM, N-CHDM would present an advanced chondrogenic potential over a reformulated ECM (S-CHDM) or TCP substrate, suggesting that N-CHDM may hold more diverse signaling cues, not just limited to ECM component.